Impact of theoretical courses on physical health performance - Mohammed Zerf (Wolters Kluwer Medknow Publications, 2016)
Background: Physical activity, health fitness, and academic results are very important goals in student life. However, success lies in academic subjects in educational establishments. Our background reveals the contradictions between two philosophers who approved the importance of physical education (PE) as a component of the curriculum and others who reiterated that PE and sports would never be a component of the curriculum as is the case in Algerian universities. Methods: The research samples were selected by the intentional manner which included sixty students, aged around 18 years. Twenty girls who will pass the baccalaureate, twenty girls of the 1 st year department languages, and twenty girls of the 1 st year PE and sports for the academic year 2014-2015 were included in the study. They were tested based on the field tests developed by the Canadian Society for Exercise Physiology. Results: Our results confirm that the absence of PE lessons and sport case department languages leads to loss of fitness in the opposite of high-school and students of the Institute of Sports, where the effects return to the absence of the session of physical education and sport. Conclusion: Physical activities are very important in the life of our scholar girls, where the sport practice is a physical as well as a mental effort which is the key to a healthier life.